A STEAM project model within the object-oriented programming discipline - GASNAS, Ala (Acta et Commentationes, Sciences of Education, 2024)
The STEM (Science, Technology, Engineering, and Mathematics) approach is a continuously expanding field, thanks to its evident benefits in the contemporary world dominated by globalization and technological advancements. Science, technology, and mathematics form the foundation for technological progress worldwide, underscoring the necessity of motivating students to engage in STEM/STEAM learning. In this article, we will explore the relevance of STEM/STEAM education, its benefits, and present a project model within the Object-Oriented Programming (OOP) discipline that can be implemented in classrooms to prepare future innovators.